The Importance of Enhancing The Indonesian House of Representatives' Oversight Role with Digital Platforms Case Study: Addressing Low Legislative Accountability Through Learning from The Estonian Parliamentary System - Hafizyah Rayfan; Hasna Wuri; Muhammad Algifari; Muhammad Nadhif (Yayasan Taslim Madayana Indonesia, 2026)
Background. The Indonesian House of Representatives (DPR) holds crucial responsibilities in supervising the government, including legislation, budgeting, and policy-making. However, a major issue lies in the lack of transparency and limited public access to information regarding legislative processes. This weakens the DPR's supervisory function and reduces legislative accountability. Purpose. The study aims to strengthen the DPR’s supervisory and legislative functions by proposing the development of a digital, integrated, and publicly accessible legislative portal. The goal is to increase transparency, public participation, and accountability in Indonesia’s legislative process. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. The study proposes that Indonesia can enhance legislative oversight by creating a real-time, interactive legislative portal that includes access to draft laws, meeting schedules, and documentation. It also emphasizes the importance of digital literacy training for both the public and DPR members and highlights that technological tools must be supported by values of openness, responsibility, and a service-oriented mindset in public governance.. Conclusion. The DPR's oversight role can be strengthened through a digital legislative platform that ensures transparency and public engagement, inspired by Estonia’s model. Beyond technology, fostering values of openness, accountability, and service is essential. This transformation requires both system reform and digital literacy for legislators and the public to ensure effective implementation.